ANALISIS STRATEGI PEMASARAN PRODUK TABUNGAN TAPENAS IB HASANAH PADA PT. BANNK BNI SYARIAH KANTOR CABANG JAKARTA UTARA - Lisa Chaerunnisah; Yulianto Yulianto (JAMBIS : Jurnal Administrasi Bisnis, 2021)
The writing of this thesis aims to analyze how the marketing strategy and the obstacles and how to solve the marketing of Tapenas Hasanah iB Savings products. The background of this thesis writing is the increasing development of the number of savings product customers in the North Jakarta Branch. However, the growth in the number of customers in Savings products is not followed in Tapenas Hasanah iB Savings Products which experienced a not significant increase compared to the previous year. It is interesting for researchers to know and analyze further how the marketing strategy and what are the constraints and solutions that influence it.In this study, researchers used descriptive qualitative research methods by means of library research and direct research in the field. This research was conducted from mid to late 2018 at PT. Bank BNI Syariah North Jakarta Branch Office. The source of information obtained by the author is the employee and customer of BNI Syariah North Jakarta Branch Office. The conclusion of this study is that the lack of promotional activities and savings programs made the Tapenas Hasanah iB Savings experience no progress. The solution is to facilitate the requirements for opening Savings and routinely increase understanding and selling skills to unit funding so that it can easily market Tapenas Hasanah iB Savings products.